Saprosma arborea Blume, a carminative plant of the community around Ujung Kulon National Park and Gunung Leuser National Park - Hasanah, Ida Farida; Kuncari, Emma Sri (Buletin Kebun Raya, 2023)
Local communities around the conservation areas of Ujung Kulon National Park (UKNP) and Gunung Leuser National Park (GLNP) believe that the leaves of Saprosma arborea Blume traditionally have carminative properties. However, public is still unfamiliar with this plant and its benefits. Literature and research on this plant are still very limited, even though S. arborea is native to Indonesia with a wide distribution area. This study aims to: (1) reveal the traditional knowledge of the community regarding how to use S. arborea as a carminative agent; (2) Conduct phytochemical screening; and (3) Test the biological activity of S. arborea leaf extract against Escherichia coli bacteria. Phytochemical screening was carried out by the Harborne method, whereas the antibacterial activity test by the agar diffusion method. There are differences in how S. arborea is used by the people around UKNP and GLNP. Communities around UKNP use it orally, while people around GLNP use it transdermally. The results of the phytochemical screening qualitatively showed that S. arborea contained several chemical compounds, such as alkaloids, tannins, flavonoids, glycosides, triterpenoids, and essential oils. Tannins, flavonoids, and essential oils contained in the leaves of S. arborea are thought to have a carminative effect. Antibacterial activity test showed that the methanol extract of S. arborea at concentrations of 500, 1000, and 1500 ppm had no antibacterial activity against E. coli.